PEMBERDAYAAN MASYARAKAT DALAM PENCEGAHAN KEBAKARAN HUTAN DAN LAHAN DI KECAMATAN KUBU KABUPATEN ROKAN HILIR - ", Azuraili; ", Zulkarnaini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Forest fire is the burning of forest area both large and small. Forest fires often occur and if they do they will burn anything nearby and follow the direction of the wind. Fire it self can occur because of two things, namely natural fires and fires caused by humans. Forest fires occur every year during the dry season. In Rokan Hilir Regency, Riau Province between 2013-2017, forest fires almost occurred throughout the year. The problem of forest fires is supported by the weak economic conditions of the community and the low level of community education which greatly affects the management of resources and the environment. So the need for empowerment efforts with the main goal is to improve the quality of life of the community. The participation of local communities in the context of preventing forest and land fires is very important. The success of forest and land fire prevention activities is highly dependent on the success of bringing local people into emotions, feelings and enthusiasm to maintain forest sustainability because the community is more in control of the location and is expected to have more responsibility because the extinguished area is the community area. The direct involvement of the community in a land and forest fire control activity can also encourage public awareness of the importance of controlling forest and land fires and can also encourage community awareness of the importance of fire control early around their area.Success in community empowerment in preventing forest and land fires in Kubu Subdistrict, Rokan Hilir Regency is the encouragement of the community to the importance of controlling forest and land fires early around their area through the formation of fire-fighting teams at the community level or anti-fire community groups that functioned to tackle forest and land fires since early in the area.The results of the study are the implementation of community empowerment in preventing forest and land fires in Kubu District, Rokan Hilir Regency, which is still less than optimal because there are still obstacles in the field, therefore there are four principles that are often used in the success of empowerment programs, namely the principle of equality, the principle of participation, self-sufficiency or independence. So that community empowerment in preventing forest and land fires in Kubu Rokan Hilir District can run optimally so that the creation of people who are empowered in preventing forest and land fires.Keywords: Forest and land fires, Empowerment, and Community.